El cantante indigena Ángel Guaraca como icono comunicacional y su incidencia en la música chicha en el sector urbano del cantón guamóte comprendido en la edad del 17 a 25 años en el periodo de Enero a Diciembre del 2014 - Angamarca Verdezoto, Kathy Marcela (2016)
The present research project tries to establish the incidence of the indigenous singer Ángel Guaraca as communicative icon in the chicha music, at the urban sector of the Guamote parish, in the young people from 17 to 25 years old. The first unit, Chicha Culture, analyzes the origin of the musical chicha, which it propitiates to what it has gone so far as to be called a chicha culture. The study of chicha music developed in Peru. In addition the Chacalón´s life one of the most recognized exponent of this style in the continent. Then, some research about the origin of the chicha music in Ecuador. The second unit, Culture and Society, theorizes terms expert culture, subculture, popular culture, to make an approach with the dissertation topic, which have an approach on communication and culture. The third unit, Guamote and Ángel Guaraca, is dedicated to study the indigenous singer origin, his musical and social influences for the production of his proposal. Also, some information about Guamote, its history and characteristics of the society composition. The fourth unit explains the data analysis and interpretations of the survey conveyed in this research project. Those who answered this question were young people from 17 to 25 years, on whom the singer Ángel Guaraca influence was determined.